Electrochemically induced surface modifications of mesoporous spinels (Co3O4−δ, MnCo2O4−δ, NiCo2O4−δ) as the origin of the OER activity and stability in alkaline medium1. Issue 33 (7th September 2015) - Abidat, I.; Bouchenafa-Saib, N.; Habrioux, A.; Comminges, C.; Canaff, C.; Rousseau, J.; Napporn, T. W.; Dambournet, D.; Borkiewicz, O.; Kokoh, K. B.
<x xml:space="preserve">Abstract</x> Oxygen deficient mesoporous cobaltites synthesized using nanocasting technique show high OER activity and surface modifications induced by potential cycling.